Release calls of four species of Phyllomedusidae (Amphibia, Anura) - Mangia, Sarah; Camurugi, Felipe; Pereira, Elvis Almeida; Carvalho, Priscila [UNESP]; Rohr, David Lucas; Folly, Henrique; Santana, Diego Jose (Pensoft Publishers, 2019)
Anurans emit a variety of acoustic signals in different behavioral contexts during the breeding season. The release call is a signal produced by the frog when it is inappropriately clasped by another frog. In the family Phyllomedusidae, this call type is known only for Pithecophus ayeaye. Here we describe the release call of four species: Phyllomedusa bahiana, P. sauvagii, Pithecopus rohdei, and P. nordestinus, based on recordings in the field. The release calls of these four species consist of a multipulsed note. Smaller species of the Pithecopus genus (P. ayeaye, P. rohdei and P. nordestinus), presented shorter release calls (0.022-0.070 s), with higher dominant frequency on average (1508.8-1651.8 Hz), when compared to the bigger Phyllomedusa (P. bahiana and P. sauvagii) (0.062-0.107 s; 798.7-1071.4 Hz). For phyllomedusid species, the release call might indicate a phylogenetic signal, because species of the same genus have similar acoustic traits.
Keywords: vocalization; animal behavior; bioacoustics; Phyllomedusa; Pithecopus